2018
DOI: 10.1007/s40520-018-0981-2
|View full text |Cite
|
Sign up to set email alerts
|

The Italian version of the quick mild cognitive impairment (Qmci-I) screen: normative study on 307 healthy subjects

Abstract: The Qmci-I is a rapid and multi-domain short cognitive screening instrument useful for evaluating cognitive functions. However, like other screening tools, it is significantly influenced by age and education, requiring normative data and correction of values when used in the clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…The MoCA-CN was significantly better able to separate MCI from dementia. The Qmci-CN represents another external validation of the instrument, after the Irish, Dutch, Australian, Turkish, Italian, Taiwanese, Japanese, and Portuguese versions (Bunt et al, 2015;O'Caoimh et al, 2016;Clarnette et al, 2017;Yavuz et al, 2017;dos Santos et al, 2019;Iavarone et al, 2019;Lee et al, 2018;Morita et al, 2019). This study adds more evidence to support its use in patients with MCI in busy clinical setting.…”
Section: Discussionmentioning
confidence: 82%
“…The MoCA-CN was significantly better able to separate MCI from dementia. The Qmci-CN represents another external validation of the instrument, after the Irish, Dutch, Australian, Turkish, Italian, Taiwanese, Japanese, and Portuguese versions (Bunt et al, 2015;O'Caoimh et al, 2016;Clarnette et al, 2017;Yavuz et al, 2017;dos Santos et al, 2019;Iavarone et al, 2019;Lee et al, 2018;Morita et al, 2019). This study adds more evidence to support its use in patients with MCI in busy clinical setting.…”
Section: Discussionmentioning
confidence: 82%
“…The effect of years of school attendance on apathy was recently described with highly educated persons obtaining lower scores during the validation of an apathy scale [ 9 ]. It is also known that years of school attendance have a significant effect on the performance on cognitive tests [ 10 , 11 ]. However, the effect of education on depression and anxiety symptoms appears in original data, and not clear evidences are reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…This paper is also one of the first, after the recent publication of the Italian version of the Q mci screen [20], to provide normative data for the Q mci screen in likely normal subjects, and this study applied a similar approach to identify likely normal participants as the Italian paper [20]. Despite the challenges of defining normative data based on sMMSE scores, there was no marked difference in median Q mci -J screen scores, after maximizing the likelihood of selecting a truly cognitively normal sample by excluding those with symptoms (both subjective and informant reported), ADL impairment or conditions known to be associated with MCI and dementia, such as stroke and Parkinson’s disease.…”
Section: Discussionmentioning
confidence: 99%
“…It was designed to minimize the floor and ceiling effects associated with the MMSE, as well as more MCI-specific CSIs such as the Montreal Cognitive Assessment (MoCA) [15,16]. Since its development and validation in Canada [16], it has been translated and validated in various languages worldwide, showing high sensitivity (0.76–0.92) and specificity (0.72–0.95) for differentiating MCI from normal cognition in a range of settings [17,18,19,20]. A recent systematic review and meta-analysis found that it compares favorably with other short CSIs specific for MCI [21].…”
Section: Introductionmentioning
confidence: 99%